Local development issues on the urban periphery: Tallaght from the bottom-up - Punch, Michael (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
The aim of this paper is to contribute to the understanding of aspects of urban social change by orientating the analysis around a grassroots-level focus . Specifically, bottom-up experiences of and responses to some of the contradictions of Dublin's new-town experiment are explored. highlighting both critical perspectives on the limits of this experiment in peripheral urban expansion and efforts to find alternative, independent solutions through bottom-up development practices. The paper first provides some contextual material in an overview of a larger research programme from which the discussion draws. It then examines some community perspectives on the problems of new-town planning as it was implemented in Tallaght on the western periphery of Dublin, drawing on qualitative analysis of interview data in order to gain some insight from the level of everyday life. The final section focuses on efforts to explore and implement alternatives through autonomous local development initiatives of various kinds.
Keywords: Urban geography -- Ireland